(untitled) (Research, Society and Development, 2022)
The theme of this article is Public Policies for Teacher Training, and the object of study is the Plano Nacional de Formação de Professores da Educação Básica - PARFOR. The study started from the following problem: In which way does PARFOR constitute itself as a compensatory neoliberal education policy that aims to (con)form the teacher-student to a marketing logic of training? The general objective is to understand how PARFOR is characterized as a neoliberal policy for teacher training. It is a preliminary study, result of research for the Thesis that will be presented to Programa de Pós-Graduação em Educação – PGEDA. This is a study with a qualitative approach, based on the Dialectical Historical Materialism (DHM) method. It is a Documentary research, which focuses on the official documents of PARFOR, as well as on the literature in the area of educational policies. The analyzes proposed reveal that PARFOR is a compensatory neoliberal policy of fast formation that is based on assumptions of individualism and blame, and that can produce the organic intellectuals of the hegemony of Capital, in a process of conformation in a market logic. This can threat the training for a transformative and socially referenced praxis.